The Role of Financial Literacy and Household Economic Resilience in Community Service Programs in the Era of Global Uncertainty - Irwan Moridu; Adrian Polim; Nurcahya Hartaty Posumah; Debiyanti Kune; Fitriani (PT. LITERASI SAINS NUSANTARA, 2025)
Global uncertainty characterized by economic fluctuations, inflation, and technological disruptions has encouraged households to develop adaptive capabilities in managing their finances. This study aims to analyze the role of financial literacy in strengthening household economic resilience through community service programs while explicitly enriching references related to community engagement within this context. The method employed is a literature review using a qualitative approach and descriptive analysis. Data were collected from Google Scholar and various credible websites covering the period from 1977 to 2026. The initial collection process yielded 50 articles, which were then rigorously screened based on relevance, quality, and contribution, resulting in 28 articles selected for further analysis. The findings indicate that financial literacy plays a significant role in shaping more structured financial behavior, improving risk management capabilities, and strengthening household economic stability. Community service programs have proven effective in transferring practical financial knowledge and skills, leading to improved saving habits, expenditure control, and utilization of formal financial services. Case studies demonstrate increases in financial literacy, financial inclusion, and changes in community economic behavior after participation in educational programs.